Blockhain Impact on Economic Security - Фень, Катерина Сергіївна; Fen, K.,Y., Z.,Ye., I. Matyskevic , Simanaviciene, Skljar , Belova; Fen, Kateryna (Independent Journal of Management & Production, 2021)
The aim of this paper is to review impact of the one of the most modern cutting edge technologies‘, namely Blockchain on Economic Security. First of all article describes concept - technological background of Blockchain technology nature, emphasizing main features that have most significant and even disruptive impact on separate industries and even whole Economy including Economic Security. Secondly contemporary challenges of this technology are provided. Thirdly multifaced concept of Economic security is explained, followed by importance of this phenomenon specifically within modern mega trends such as Globalization and Information Society. Blockhain impact has been researched through three main industries/functions – eCommerce, Payments and Logistics. Finally conclusions of the paper suggest to use Blockhain with another Industry 4.0 technologies (such as Big Data and Internet of Thing) to reach maximum possible synergy.
Blockhain Impact on Economic Security
Keywords: Blockchain Economic security Industry 4.0 Digital technologies digitalization